Evolution of antifungal drug resistance in Candida albicans - Barbosa, Mónica Rodrigues (2018)
The human pathogen Candida albicans is characterized by the presence of a hybrid tRNA (tRNACAGSer) that can be aminoacylated by both LeuRS and SerRS. This tRNA is responsible for the ambiguity of the CUG codon that can be decoded as serine (97%) and Leucine (3%). Previous studies showed that the level of ambiguity is variable depending on the growth condition of the fungus. These studies also revealed that strains mistranslating at a higher level grew better in the presence of azoles, particularly in the presence of fluconazole. To analyse the effect of translation errors on the acquisition of drug resistance, three strains of C. albicans were used (T0, T1 and T2). These strains have increasing levels of Leu misincorporation and were constructed by inserting a copy (T1) or two copies (T2) of a tDNACAG Leu gene. These strains were evolved experimentally in the presence and absence of the antifungal agent according to the approved EUCAST protocol. The level of ambiguity of all strains was measured along the evolution experiment, using a reporter system based on the green fluorescent protein (GFP). Finally, the type of acquired resistance was also evaluated (genetic or phenotypic resistance). Experimental data suggest that the acquisition of resistance is dependent on the drug and the percentage of mistranslation. Strains with increased mistranslation (T2) acquired more resistance (256 μg/ml) and faster than the control T0. Mutations in ERG11 gene might be responsible for this resistance. Also, T2 strain showed a decrease in the mistranslation level during both evolution experiments (with and without drug) as a consequence of the deletion of one of the two copies of the mutant tDNACAG Leu gene. This result further highlights the genetic instability of strain T2.